Fantastic Mr. Fox - Dahl, Roald; Blake, Quentin (New York : Puffin Books, 2016)
Three farmers, each one meaner than the other, try all-out warfare to get rid of the fox and his family.
Includes excerpt from James and the Giant Peach.
600
Accelerated Reader AR
Keywords: Foxes -- Juvenile fiction; Farmers -- Juvenile fiction; Humorous fiction